Acting in time on energy policy [electronic resource] - Gallagher, Kelly Sims (Brookings Institution Press, 2009)
"Details the often incomplete, incoherent, and ineffectual U.S. energy policy, tackling specific policy questions: Why are these components of energy policy so important? How would 'acting in time'--not waiting until politics demands action--make a diff